Comparison of stroke volumes assessed by three-dimensional echocardiography and transpulmonary thermodilution in a pediatric animal model - Linden, Katharina; Ladage, Dennis; Dewald, Oliver; Gatzweiler, Eva; Pieper, Andrea; Seehase, Matthias; Duerr, Georg Daniel; Breuer, Johannes; Herberg, Ulrike (Journal of Clinical Monitoring and Computing, 2017)
To compare stroke volumes (SV) in small hearts assessed by real-time three-dimensional echocardiography (3DE) with SV measured by transpulmonary thermodilution (TPTD) and continuous pulse contour analysis (PC) under various hemodynamic conditions. In thirteen anesthetized piglets (range 3.6–7.1 kg) SV were measured by 3DE, TPTD and PC at baseline and during phenylephrine and esmolol administration. 3DE and TPTD measurements were done successively while SV calculated by PC was documented at the time of 3DE. 3DE and TPTD showed a good correlation (r2 = 0.74) and a bias of −1.3 ml (limits of agreement −4.1 to 1.5 ml). While TPTD measured higher SV than 3DE, both methods tracked SV changes with a concordance rate of 91 %. PC and 3DE showed a lower correlation coefficient of r2 = 0.57 and a bias of −2.1 ml (limits of agreement −5.9 to 1.8 ml). Inter- and intra-observer variability of SV measured by 3DE was good with a mean bias <5 %. SV3DE showed a small variance and tracked acute small changes in SV in acceptable concordance with TPTD. PC measured SV with a higher variance and mean difference compared to 3DE. In an experimental setting 3DE has the possibility to offer non-invasive assessments of ventricular volumes volume changes. To determine whether 3DE could be used for SV assessment in a clinical routine our results need confirmation in a clinical setting.
CRIS-Team Scopus Importer:2022-05-03
Keywords: 3-Dimensional echocardiography; Hemodynamics; Pulse contour analysis; Small hearts; Stroke volume; Transpulmonary thermodilution